Kotobee author para el aprendizaje de invertebrados en estudiantes de cuarto semestre de la Carrera de Pedagogía de las Ciencias Experimentales Química y Biología - Allas Chisag, Wellinton Danilo (2024)
Education today has evolved and with it the use of new innovative digital resources, the current problem originated when teachers when sharing their knowledge in the classroom use basic software such as Power Point, Genially, Canva, etc. and do not seek alternatives to attract the student's attention. The objective of the research was to propose Kotobee author to improve the learning of invertebrate animals. The type of research was quantitative, the research design was non-experimental, descriptive and explanatory, bibliographic and field type. For data collection, the survey technique was used and the questionnaire was used as an instrument. The sample consisted of 28 students of the fourth semester of the Pedagogy of Experimental Sciences, Chemistry and Biology of the National University of Chimborazo. A digital book was designed using Kotobee Author software, which addressed the topics and subtopics related to the syllabus of the Animal Biology course. Finally, it was concluded that the use of the digital book designed was innovative because it awakens curiosity in the students, helped them to learn about invertebrate animals and generated a greater interest in the subject of Animal Biology.